Моделирование диффузионного переноса в среднеширотной области F ионосферы - Дзюбанов, Дмитрий Анатольевич; Ляшенко, Михаил Владимирович; Мирошников, Артем Евгеньевич (НТУ "ХПИ", 2010)
У статті розглядається моделювання вертикальної складової швидкості дифузійного переносу іоносферної плазми. Аналізується внесок кожної складової у виразі для дифузійної швидкості, які зумовлені впливом градієнтів електронної концентрації, температур заряджених частинок, а також сил гравітаційного тяжіння, при різних рівнях сонячної активності.

The article deals with simulation of the vertical component of the diffusion velocity of the ionospheric plasma. We analyze the contribution of each term in the expression for the diffusion velocity due to the influence of pressure gradients caused by a high-altitude change of the electron density, temperature of the charged particles, force of gravitational attraction and changes in the height of the atmosphere of the plasma, at different levels of solar activity.
Keywords: ионосферная плазма; диффузионная скорость; ионосферные параметры; солнечная активность; концентрация электронов; температура заряженных частиц; глобальная атмосферная циркуляция